2017
DOI: 10.1080/0284186x.2017.1324207
|View full text |Cite
|
Sign up to set email alerts
|

A review of dosimetric and toxicity modeling of proton versus photon craniospinal irradiation for pediatrics medulloblastoma

Abstract: Proton-CSI conferred better treatment outcomes than Photon-CSI for pediatric medulloblastoma patients. This review serves to compare the current literature in the absence of long-term data from prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Translation into quality of life (QoL) has been studied in a prospective trial 111. QoL scores were found to improve over time after proton CSI, and after 5 years, children-reported scores were statistically similar to those of healthy children, but the parent-reported scores remained statistically lower than those reported by the parents of healthy children 112. To evaluate the superiority of proton therapy in medulloblastoma treatment with an evidence-based approach, a review recently compared the outcomes of pediatric medulloblastoma patients between proton- and photon-mediated CSI,113 and revealed the advantage of proton therapy in organs at risk sparing, normal organ dysfunction, and secondary malignancy risks compared to various (mostly 3D-CRT) photon techniques.…”
Section: Optimizing Care From Molecular Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Translation into quality of life (QoL) has been studied in a prospective trial 111. QoL scores were found to improve over time after proton CSI, and after 5 years, children-reported scores were statistically similar to those of healthy children, but the parent-reported scores remained statistically lower than those reported by the parents of healthy children 112. To evaluate the superiority of proton therapy in medulloblastoma treatment with an evidence-based approach, a review recently compared the outcomes of pediatric medulloblastoma patients between proton- and photon-mediated CSI,113 and revealed the advantage of proton therapy in organs at risk sparing, normal organ dysfunction, and secondary malignancy risks compared to various (mostly 3D-CRT) photon techniques.…”
Section: Optimizing Care From Molecular Classificationmentioning
confidence: 99%
“…The only way to determine with any certainty whether proton therapy should be developed as a standard of care for CSI would be through a prospective randomized controlled trial comparing both treatment modalities. Such a trial should include cost-effectiveness analysis since proton therapy is undoubtedly associated with higher initial infrastructural costs than those for photon therapy 112. At the present time, proton therapy remains a limited resource, and socioeconomic factors impact access to this treatment 113…”
Section: Optimizing Care From Molecular Classificationmentioning
confidence: 99%
“…Besides continuous advances in image-guided (IG) intensity-modulated (IM) photon radiotherapy, particle therapy with protons is establishing itself as a high-conformal RT modality which is able to improve normal tissues dose sparing while maintaining excellent target coverage [5]. Indeed, thanks to the physical characteristics of protons—such as the typical dose distribution within the “Bragg peak” [6], Proton Beam Therapy (PBT) could represent a safe alternative to photon RT for pediatric tumors or other neoplasms arising next to critical OARs [1]. Nevertheless, radiobiological uncertainties about the interaction of these charged particles with normal and neoplastic cells still persist [6].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, proton therapy has emerged as a major RT modality for the treatment of medulloblastoma. Multiple dosimetric studies of RT for medulloblastoma have demonstrated the superior dose distribution of protons as compared to photons [65], and emerging clinical evidence suggests that proton-based CSI/boost therapy for pediatric patients with medulloblastoma reduces acute and late effects without reducing tumor control [66][67][68][69][70].…”
Section: Advances In Radiotherapy Techniquesmentioning
confidence: 99%